Cardiovascular disease risk profile and management among people 40 years of age and above in Bo, Sierra Leone: A cross-sectional study. - Maria Lisa Odland; Khadija Gassama; Tahir Bockarie; Haja Wurie; Rashid Ansumana; Miles D Witham; Oyinlola Oyebode; Lisa R Hirschhorn; Justine I Davies (PLoS ONE, 2022)
Introduction Access to care for cardiovascular disease risk factors (CVDRFs) in low- and middle-income countries is limited. We aimed to describe the need and access to care for people with CVDRF and the preparedness of the health system to treat these in Bo, Sierra Leone. Methods Data from a 2018 household survey conducted in Bo, Sierra Leone, was analysed. Demographic, anthropometric and clinical data on CVDRF (hypertension, diabetes mellitus or dyslipidaemia) from randomly sampled individuals 40 years of age and above were collected. Future risk of CVD was calculated using the World Health Organisation-International Society of Hypertension (WHO-ISH) calculator with high risk defined as >20% risk over 10 years. Requirement for treatment was based on WHO package of essential non-communicable (PEN) disease guidelines (which use a risk-based approach) or requiring treatment for individual CVDRF; whether participants were on treatment was used to determine whether care needs were met. Multivariable regression was used to test associations between individual characteristics and outcomes. Data from the most recent WHO Service Availability and Readiness Assessment (SARA) were used to create a score reflecting health system preparedness to treat CVDRF, and compared to that for HIV. Results 2071 individual participants were included. Most participants (n = 1715 [94.0%]) had low CVD risk; 423 (20.6%) and 431 (52.3%) required treatment based upon WHO PEN guidelines or individual CVDRF, respectively. Sixty-eight (15.8%) had met-need for treatment determined by WHO guidelines, whilst 84 (19.3%) for individual CVDRF. Living in urban areas, having education, being older, single/widowed/divorced, or wealthy were independently associated with met need. Overall facility readiness scores for CVD/CVDRF care for all facilities in Bo district was 16.8%, compared to 41% for HIV. Conclusion The number of people who require treatment for CVDRF in Sierra Leone is substantially lower based on WHO guidelines compared to CVDRF. CVDRF care needs are not met equitably, and facility readiness to provide care is low.